The Role of Emotional Brand Attachment and Customer Trust in Enhancing Customer Experience’s Effect on Customer Loyalty Towards Beauty Clinics in Surabaya - Endah Kartika Sari; Serli Wijaya (Master of Management, School of Business and Management, Petra Christian University, 2019)
The growth of beauty and personal care products users in Indonesia has been increasing significantly in the past five years, higher than the indutry’s growth globally. This fact shows that cosmetics and skincare business in the country has a positive outlook in the years ahead. The increasing number of beauty clinics brands in the market has led to the more intense competition. Consumers are offered with more options to treat themselves better through personal care and beauty services. In order to survive in today’s competitive industry, customer loyalty becomes a paramount. Literature has shown that customer loyality is formed by many factors such as experience, trust and emotional attachment between the customers and the services providers. This study aimed to investigate the influence of customer experience on customer loyalty towards beauty clinics in Surabaya by examining the aspects of customers’ emotional brand attachment and trust. The results showed that there was a positive and significant effect of customer experience on emotional brand attachment and customer trust, which in turn, leading to a significant and positive effect on customer loyalty.